Development of a magnetic-geared permanent-magnet brushless motor - Wang, Lili; Shen, Jian-Xin; Luk, Patrick Chi-Kwong; Fei, Wei-Zhong; Wang, Can-Fei; Hao, He (IEEE, 2009)
High-torque and low-speed electrical drives are often employed for applications where mechanical gearing cannot be accommodated. On the other hand, permanent-magnet (PM) gear has drawn significant attention from both academies and industries due to the conspicuous merits, such as reduced acoustic noise, maintenance free, improved reliability, precise peak torque transmission capability, and inherent overload protection. In this paper, a magnetic-geared PM brushless motor is presented. It is a novel low-speed and high-torque motor which merges the advantages of conventional PM brushless motor and PM gear. Its topology and operation principle are introduced. Some techniques are employed to optimize and improve the motor performance, while the validity of the proposed techniques is verified with finite-element analysis. Moreover, an alternative operation condition, which can further reduce the motor speed and increase its output torque, is proposed and analyzed.
Keywords: Direct drive finite-element analysis high torque low speed magnetic gear permanent-magnet (PM) motor design